Development of transformation bands in ceria-stabilized-zirconia based composites during bending at room temperature. Issue 1 (January 2021) - Liens, Aléthéa; Swain, Michael; Reveron, Helen; Cavoret, Jérôme; Sainsot, Philippe; Courtois, Nicolas; Fabrègue, Damien; Chevalier, Jérôme
Abstract: Transformation-induced plasticity in a ceria-stabilized-zirconia based composite was studied in four-point bending, with particular emphasis on nucleation and growth of tetragonal-to-monoclinic transformation bands. They initiated on the side in tension at a given value of stress and grow in size and number with increased applied load. The spacing between them was related to samples' thickness: thicker samples led to a smaller number of larger/deeper bands. Residual stresses around indentations, placed on the tensile surface of some samples, triggered transformation bands nucleation but had no significant effect on the final total number of bands. A simple stress shielding model suggests that wide bands hinder adjacent thinner bands to propagate and expand because of stress shielding around them. Nucleation of a given transformation band is thus related to: (i) stress concentrations at the surface, (ii) geometry (stress-field inside the sample) and (iii) a shielding effect from the bands already present.